Types and Forms of Independent Work in the Organization of Educational Activities of Students on the Subject "Descriptive Geometry and Engineering Graphics" - Ugiloy Nabievna Sultonova; Safar Nabievich Sultonov (International Journal on Integrated Education, 2022)
At present, special attention is paid to the formation and development of independent learning activities of students in the subject "Descriptive Geometry and Engineering Graphics". It was noted that the formation and development of independent learning activities of students in the disciplines of "Descriptive Geometry and Engineering Graphics" and "Engineering and Computer Graphics" play an important role in increasing the effectiveness of teaching.